Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0022002715615190
|View full text |Cite
|
Sign up to set email alerts
|

Theme and Variations

Abstract: Since its establishment in 1963, the Correlates of War (COW) project has sought to build cumulative knowledge about international conflict through the application of the scientific method to the study of militarized interstate behavior. Early analyses from the COW project found substantial variation in the causal model of war across the nineteenth and twentieth centuries, but COW scholars later sought to develop a general model of war that avoided post hoc historical periodization. We use out of sample cross v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As the dataset includes interstate conflicts over the past 200 years (1816–2014), a question arises: Is the power-law exponent consistent or changing over the past 200 years? A recent study conducting out-of-sample cross-validation demonstrated that causal models of war vary periodically 40 . To address this, we also examined the power-law hypothesis by dividing the entire period (1816–2014) into the following eras: (i) the first half of the nineteenth century (1816–1858); (ii) the second half of the nineteenth century (1859–1899); (iii) the first half of the twentieth century lasting from 1900 to just after WWII (1946); (iv) the Cold War era (1947–1989), and (v) the post-Cold War era (1990 ~ the present (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…As the dataset includes interstate conflicts over the past 200 years (1816–2014), a question arises: Is the power-law exponent consistent or changing over the past 200 years? A recent study conducting out-of-sample cross-validation demonstrated that causal models of war vary periodically 40 . To address this, we also examined the power-law hypothesis by dividing the entire period (1816–2014) into the following eras: (i) the first half of the nineteenth century (1816–1858); (ii) the second half of the nineteenth century (1859–1899); (iii) the first half of the twentieth century lasting from 1900 to just after WWII (1946); (iv) the Cold War era (1947–1989), and (v) the post-Cold War era (1990 ~ the present (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…(Jackson & Morelli, 2011). This decontextualized game theory, founded on rational action and a capitalist consumer mentality, dominates the deracinated world of mainstream political science -the reductive, selfish side to rationality (Altman, 2015;Meadwell, 2015). Psychological explanations have also been diminished to these game-theoretical assumptions and artificial experiments (Böhm, Rusch, & Gürerk, 2015), while cliometricians, too, are subject to the warlockcraft's imposing spells (Eloranta, 2016;Jenke & Gelpi, 2016).…”
Section: Why Do Wars Happen?mentioning
confidence: 99%